Relationships between Malaysian food image, tourist satisfaction and behavioral intention. - Leong, Quee Ling; Ab. Karim, Muhd. Shahrim; Othman, Mohhidin; Mohd Adzahan, Noranizan; Sridar, Ramachandran (IDOSI Publications, 2010)
This study aims to examine tourists’ satisfaction towards Malaysian food and their future behavioural intentions. A survey was carried out at the Kuala Lumpur International Airport (KLIA) and Low Cost Carrier Terminal (LCCT) in Malaysia. A sample of 392 tourists was obtained at the respective departure halls using systematic sampling approach. The findings indicated that Malaysia has the potential of being a food tourism destination as the country is viewed as a melting pot of cultural food variety at reasonable price. In addition, the results reveal that image has a direct effect on satisfaction and tourists’ satisfaction towards Malaysian food has a direct effect on behavioural intention. The findings, strengthens the notion of repeat visitation to experience the unique food culture. Practical and theoretical contributions are discussed, with future research suggested.